Investigation on Corrosion Resistance of Welded Cu-Bearing 304L Stainless Steel Against Pseudomonas aeruginosa - Yin, Lu; Xi, Tong; Yang, Chunguang; Zhao, Jinlong; Sun, Yupeng; Zhao, Hanyu; Yang, Ke (Frontiers in Materials, 2020)
In this work, the microbiologically influenced corrosion (MIC) behaviors of welded 304L stainless steel (304L SS) and Cu-bearing 304L stainless steel (304L-Cu SS) in a Pseudomonas aeruginosa (P. aeruginosa) culture medium were comparatively studied. Open circuit potential (OCP), linear polarization (LPR), electrochemical impedance spectroscopy (EIS) and potentiodynamic polarization were employed to characterize the corrosion behaviour of the (welded) steel substrates. The biofilm morphology and the live/dead staining condition of the sessile cells were observed by scanning electron microscopy (SEM) and confocal laser scanning microscopy (CLSM). And the pitting corrosion was investigated with a 3D mode of CLSM. The experimental results showed that the copper (Cu) addition had no obvious influence on the microstructure of 304L SS in welding zones and base metal. The welding zones of 304L SS and 304L-Cu SS in sodium chloride solution possessed a lower pitting potential and a higher corrosion current density. However, due to the continuous release of Cu ions, inhibiting the excretion of corrosive extracellular polymeric substances (EPS) and the extracellular electron transport (EET) process, both the localized and uniform corrosion attack induced by the P. aeruginosa biofilm were significantly reduced. In comparison with 304L SS, the corrosion resistance of 304L-Cu SS in the welding zone against P. aeruginosa was obviously higher.